1990
DOI: 10.1007/bf00196232
|View full text |Cite
|
Sign up to set email alerts
|

Unusual X chromosome inactivation in a mentally retarded girl with an interstitial deletion Xq27: implications for the fragile X syndrome

Abstract: A de novo interstitial deletion (X)(q27.1q27.3), between the loci DXS 105 and F8, has been found in a mentally retarded female. The deleted X chromosome is preferentially early replicating in fibroblasts, B cells and T cells, suggesting that the missing region plays a role in inactivation of the X chromosome. None of the available DNA probes except DXS 98 maps to the deleted region of about 10,000 kb. The locus FRAXA is either included in the deletion, or located close to the distal break point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This data of Mohandas et al (1987) could be interpreted as indicating that the region Xq26.3-qter is capable of undergoing inactivation autonomously and not by spreading from other parts of the X chromosome. Since we have previously reported a deletion of Xq27 associated with preferential activity of the deleted chromosome (Schmidt et al 1990), we wondered whether the distal Xq is not involved in the X inactivation process. Therefore, we decided to determine whether this or other X regions are subject to inactivation when in a double copy on a single X chromosome in a genome.…”
Section: Introductionmentioning
confidence: 99%
“…This data of Mohandas et al (1987) could be interpreted as indicating that the region Xq26.3-qter is capable of undergoing inactivation autonomously and not by spreading from other parts of the X chromosome. Since we have previously reported a deletion of Xq27 associated with preferential activity of the deleted chromosome (Schmidt et al 1990), we wondered whether the distal Xq is not involved in the X inactivation process. Therefore, we decided to determine whether this or other X regions are subject to inactivation when in a double copy on a single X chromosome in a genome.…”
Section: Introductionmentioning
confidence: 99%
“…Fragile X analysis revealed that each of the females had completely nonrandom X inactivation with only the normal X chromosome as the active one [5]. However, there are a few reports about girls with intellectual disabilities and microdeletion of Xq27.3 whose X inactivation pattern did not show complete skewing of X inactivation in favor of the normal X chromosome, probably because of the smaller sized deletions in these patients [6,7].…”
Section: Discussionmentioning
confidence: 93%
“…The human x hamster hybrid cell line 908K1B17 and the human x mouse hybrid cell lines LC12K15 and CY34, used for the regional localization of II-10, have been described in detail previously (Schonk et al 1989;Suthers et al 1989Suthers et al , 1990Schmidt et al 1990).…”
Section: Methodsmentioning
confidence: 99%